Cell Type- and Sex-Dependent Transcriptome Profiles of Rat Anterior Pituitary Cells - Fletcher, Patrick A.; Smiljanic, Kosara; Maso Prévide, Rafael; Iben, James R.; Li, Tianwei; Rokic, Milos B.; Sherman, Arthur; Coon, Steven L.; Stojilkovic, Stanko S. (Frontiers in Endocrinology, 2019)
Understanding of physiology and pathology of an organ composed of variety of cell populations depends critically on genome-wide information on each cell type. Here, we report single-cell transcriptome profiling of over 6800 freshly dispersed anterior pituitary cells from postpubertal male and female rats. Six pituitary-specific cell types were identified based on known marker genes and characterized: folliculostellate cells and hormone producing corticotrophs, gonadotrophs, thyrotrophs, somatotrophs, and lactotrophs. Also identified were endothelial and blood cells from the pituitary capillary network. The expression of numerous developmental and neuroendocrine marker genes in both folliculostellate and hormone producing cells supports that they have a common origin. For several genes, the validity of transcriptome analysis was confirmed by qRT-PCR and single cell immunocytochemistry. Folliculostellate cells exhibit impressive transcriptome diversity, indicating their major roles in production of endogenous ligands and detoxification enzymes, and organization of extracellular matrix. Transcriptome profiles of hormone producing cells also indicate contributions toward those functions, while also clearly demonstrating their endocrine function. This survey highlights many novel genetic markers contributing to pituitary cell type identity, sexual dimorphism, and function and points to relationships between hormone producing and folliculostellate cells.